Harmonization of takeovers in the internal market: an analysis in the light of EU law - Papadopoulos, T (2010)
This DPhil thesis analyses the Takeover Bid Directive in the light of EU Law and examines the extent to which this Directive facilitates the exercise of the fundamental freedom of establishment and the free movement of capital in the internal market. Since the Directive is based on the EC Treaty chapter on freedom of establishment (Articles 43 and 44(2)(g) EC Treaty), it should in principle contribute to cross frontier corporate mobility in the internal market through takeover bids; this was the aim of the Commission in its various proposals. Takeover bids and the EC Treaty provisions on freedom of establishment are closely related. The Directive forms part of the EU company law harmonization programme whose weaknesses and limits are also explored. However, the Takeover Bid Directive is an EU company law instrument with strong links to EU capital market law. The initial aims of the EU legislature were to establish an internal market for companies and to achieve market integration in the field of EU company law. However, the Takeover Bid Directive is a compromise and watered down version of a proposal which the Commission envisaged would lead to a more effective pan-European takeover regime than that which actually proved possible. The need for compromise was the result of the very different legal and policy approaches of the Member States in the field of takeover regulation. Some provisions of the Directive are obligatory for all Member States. These provisions include the mandatory bid rule, the squeeze-out right, and the sell-out right. All these obligatory provisions of the Directive are in their present form open to criticism. The two key provisions of the Directive have been made optional for Member States. These are the non-frustration rule, requiring the board to obtain the prior authorization of the general meeting of shareholders before taking any action which could result in the frustration of the bid; and the breakthrough rule, requiring that any restrictions on the transfer of securities or voting rights provided for in the articles of association of the offeree company or in contractual agreements between the offeree company and the holders of its securities or in contractual agreements between holders of the offeree company’s securities shall not apply vis-à-vis the offeror during the time allowed for acceptance of the bid. Nevertheless, Member States, which opt out, are obliged to allow individual companies to opt in. Moreover, a reciprocity rule was also adopted, which allows Member States to permit those companies, which apply these provisions, to opt out again if they are the target of a bidder, which does not itself apply the same takeover provisions. Additionally, the non-frustration and the breakthrough rule are not fully comprehensive and even when a company applies them, it might still be able to evade their application since some corporate and financial structures remain outside the Directive’s scope. Finally, this thesis discusses the extent to which obstacles to cross border takeovers addressed by the Directive, or indeed left intact by the Directive, are to be regarded as restrictions on the right of establishment stricto sensu, or simply as obstacles in practice to making a successful takeover bid. More specifically, it scrutinizes the horizontal direct effect of the EC fundamental freedoms and seeks to analyze the extent to which conduct of the board and articles in the corporate constitution might be said to constitute restrictions on the freedom of establishment and on the free movement of capital.